Sexual and reproductive health service utilization and associated factors among youth workers at Kombolcha Industry Park, Kombolcha town, Northeast Ethiopia, 2023 - Endalew, Addisu; Kefale, Bereket; Atnafu Gebeyehu, Natnael; Birhan, Belete (Frontiers in Public Health, 2024)
Background: Youth is a decisive age to shape the direction of their life and that of their family. However, due to the host of biological, social, and economic factors, youth industry park workers can be at high risk of adverse sexual and reproductive health outcomes. Therefore, assessing youth sexual and reproductive health service utilization and associated factors among youth workers is very crucial for timely intervention to their gaps. Objective: To assess sexual and reproductive health service utilization and associated factors among youth workers working at Kombolcha Industry Park Kombolcha, Northeast Ethiopia, 2023. Methods: An institutional -based cross-sectional study were conducted at Kombolcha Industry Park, Kombolcha, from a total of 422 youth workers from January 1 to January 30, 2023. A simple random sampling technique was used to access a total of 422 youth workers in Kombolcha Industry Park. The data were collected using pre-test, structured, and interviewer-administered questionnaires. Data were entered into Epi Data version 3.1 and was exported to SPSS version 26 for analysis. Bi-variable and multivariable Binary logistic regression were performed. Adjusted odds ratio with 95% confidence interval was estimated to measure the strength of the association. The level of statistical significance was declared at a p value of less than 0.05. Results: Overall utilization of reproductive health service was 45.50%. Being married (AOR = 5.76, 95% CI (2.94, 11.25)), near distance of SRH facility to home (AOR =2.57, 95% CI (1.60, 4.14)), having good knowledge (AOR=9.23 95%CI (4.88, 17.44)) and good attitude about SRH (AOR=2.06 95% CI (1.29, 3.28)) were significantly associated with youth SRHs utilization. Conclusions Youth sexual and reproductive health service utilization among youth workers of Kombolcha Industry Park was low. Ensuring SRHs availability and accessibility and empower youth with knowledge of SRHs and advocating sexual and reproductive health service to develop good attitude might be important in improving reproductive health service utilization. Future researcher should address segment of population other that Kombolcha Industry Park.